The Roman necropolis of Kom Abu Billu (Egypt): an overview of ceramic material in funerary context - Simony, Aude (Rei Cretariae Romanae Fautorum Acta, 2024)
Since 2012, research has been carried out by the French Mission led by S. Dhennin (CNRS, HiSOMA) on the site of Kom Abu Billu, located on the western edge of Egyptian Delta in Menoufia Governorate. Recent archaeological excavations have focused mainly on the western part of the site, especially on the Greco-Roman necropolis area (Sector 2), revealing a remarkable number of artefacts in association with mud-bricks tombs, mainly ceramic vessels, but also lamps, terracotta figurines, faience and glass containers, and metallic objects. Most of these elements were very probably part of the funerary equipment of the burials. Thus, this paper aims at presenting and exploring the specificity of locally produced Roman pottery from one of the largest Greco-Roman necropolises of Lower Egypt.